COASTAL WOMEN AND THE POTENTIAL OF SMALL-SCALE FISH PRODUCT PROCESSING VENTURES - Rathnakumar, Rathnakumar Balasundari (International Journal of Allied Sciences (IJAS), 2023)
In the coastal regions of Tamil Nadu, fisherwomen primarily rely on vending freshly caught fish to make their livelihood. However, this is often not economically viable as they must sell their catch within a day, sometimes at a basic cost that does not even cover their expenses due to the short shelf life of raw fish. To overcome this challenge and increase their income, coastal women can explore small-scale fish product processing as a promising business opportunity. Value addition of seafood products can be achieved through the production of fish pickle, fish incorporated pasta, fish incorporated noodles, and Ready-To-Eat Fish curry. The manufacturing procedures for these value-added seafood products are simple and can significantly increase the income of the fisherwomen. Moreover, such products not only cater to the growing consumer base seeking nutritious and diverse fish-based foods but also provide health benefits to the consumers. Furthermore, the younger generation is constantly looking for new, easily available, and accessible products, making this field an excellent opportunity for entrepreneurial development among coastal women. By engaging in small-scale fish product processing, these women can enhance their personal capabilities and contribute to societal improvement. Such businesses can help empower coastal women, ensuring a more sustainable livelihood and better prospects for their families and communities.